UNLOCKING COOPERATIVE POTENTIAL: A STUDY ON CAPITAL STRUCTURES AND BUSINESS PERFORMANCE - Azhari, Azhari (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2025)
Cooperatives play an important role in the Indonesian economy, but many cooperatives face challenges in improving their business performance. Optimal capital structure is believed to influence the success of cooperatives, but few studies have examined the short-term and long-term relationships between internal capital, external capital, and business volume on cooperative performance. This study aims to identify the effect of capital structure and business volume on cooperative performance, using Residual Income (SHU) or profit as the main indicator of success. The method used is Autoregressive Distributed Lag (ARDL) to analyze annual data of cooperatives in Indonesia from 2000 to 2023. The results show that internal capital and business volume significantly positively affect profit, while external capital only has an effect in the long run. The implications of these findings highlight the importance of a balance between internal and external capital as well as an increase in business volume to promote cooperative success. This study also reveals limitations related to data representation that only cover cooperatives with available financial statements and periods. Therefore, further research involving broader data and additional variables is needed to deepen the understanding of the factors affecting cooperative performance